(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The paper argues that in Africa, the storyteller discursively functions as an actor, director, a producer, and all. It investigates the point of emergence and the point of departure between the storyteller in Ghana and that of the Western theatre stage performer, director and producer. The study regards the storytelling art as a literary theory which is an intellectual knowledge paradigm grounded in values derived from indigenous cultural experiences of the storyteller. By analysing and drawing particular attention to roles of the storyteller, this article expresses perspectives, based upon the values of using all the necessary communication skills as a viable medium to spur people into action for self-actualisation. The paper attempts to show the strong intertextual and interconnection between both Ghanaian (African) theatre and the Western theatre experiences. The selected areas in the paper suggest direct and indirect identical traits and weighing strength of thoughts and practices of the storyteller’s various roles, and also to fix those roles into various functions in the Western theatre. Implications are drawn on the basis of the critically examined experiences and through analysis of the utilisation of the oral Ghanaian (African) storytelling traditions as a methodological framework. This study, therefore, highlights the basic functions and roles in the Western theatres which the storyteller performs through the development of the dramatic storytelling theatre.